Assignment 6

Table of Contents

The following assignment is due Thursday 3/27 by 8:00 PM. You'll need to submit a pdf file on Gradescope.

1. Soundness of IPL

Recall the proof system IPL:

\begin{align*} \frac {} {\Gamma, \phi, \Delta \vdash \phi} \text{(assumption)} \qquad \frac {\Gamma \vdash \bot} {\Gamma \vdash \phi} \text{($\bot$-elim)} \end{align*} \begin{align*} \frac {\Gamma, \phi \vdash \psi} {\Gamma \vdash \phi \to \psi} \text{($\to$-intro)} \qquad \frac {\Gamma \vdash \phi \to \psi \qquad \Gamma \vdash \phi} {\Gamma \vdash \psi} \text{($\to$-elim)} \end{align*} \begin{align*} \frac {\Gamma \vdash \phi \qquad \Gamma \vdash \psi} {\Gamma \vdash \phi \land \psi} \text{($\land$-intro)} \qquad \frac {\Gamma \vdash \phi \land \psi} {\Gamma \vdash \phi} \text{($\land$-elim$_0$)} \qquad \frac {\Gamma \vdash \phi \land \psi} {\Gamma \vdash \phi} \text{($\land$-elim$_1$)} \end{align*} \begin{align*} \frac {\Gamma \vdash \phi} {\Gamma \vdash \phi \lor \psi} \text{($\lor$-intro$_0$)} \qquad \frac {\Gamma \vdash \psi} {\Gamma \vdash \phi \lor \psi} \text{($\lor$-intro$_1$)} \end{align*} \begin{align*} \frac {\Gamma \vdash \phi \lor \psi \qquad \Gamma, \phi \vdash \xi \qquad \Gamma, \psi \vdash \xi} {\Gamma \vdash \xi} \text{($\lor$-elim)} \end{align*}

Prove the soundness theorem for IPL. That is, prove that if \(\Gamma \vdash \phi\) according to the above rules, then \(\Gamma \vDash \phi\). You should use induction on the structure of the derivation of \(\Gamma \vdash \phi\).

2. Weakening in STLC

Recall the type system STLC:

\begin{align*} \frac {} {\Gamma, x : A, \Delta \vdash x : A} \text{(assumption)} \qquad \frac {\Gamma, x : A \vdash M : B} {\Gamma \vdash \lambda x . M : A \to B} \text{($\to$-intro)} \end{align*} \begin{align*} \frac {\Gamma \vdash M : A \to B \qquad \Gamma \vdash N : A} {\Gamma \vdash M N : B} \text{($\to$-elim)} \end{align*}

Prove that weakening is an admissible rule in STLC. Recall that the weakening rule is written as:

\[ \frac {\Gamma \vdash M : A} {\Gamma, x : B \vdash M : A} \text{(weakening)} \]

where 𝑥 does not appear in Γ and 𝐵 is a simple type. You should prove this by induction on the structure of the derivation of Γ ⊢ 𝑀 ∶ 𝐵. (Hint. You may want to prove the stronger fact that we can introduce a variable anywhere in the context Γ and not just at the end)

3. A Variant of Linear Logic

Consider the following proof system:

\[ \frac {} {\phi \vdash \phi} \text{(start)} \qquad \frac {\Gamma \vdash \phi} {\pi(\Gamma) \vdash \phi} \text{(exchg)} \]

\[ \frac {\Gamma, \phi \vdash \psi} {\Gamma \vdash \phi \to \psi} \text{($\to$-intro)} \qquad \frac { \Gamma \vdash \phi \to \psi \qquad \Delta \vdash \phi } { \Gamma, \Delta \vdash \psi } \text{($\to$-elim)} \] \[ \frac { \Gamma \vdash \phi \qquad \Delta \vdash \psi } {\Gamma, \Delta \vdash \phi \land \psi} \text{($\land$-intro)} \qquad \frac { \Gamma \vdash \phi \land \psi \qquad \Delta, \phi, \psi \vdash \xi } { \Gamma, \Delta \vdash \xi } \text{($\land$-elim)} \] \[ \frac {\Gamma \vdash \phi} {\Gamma \vdash \phi \land \phi} \text{(clone)} \qquad \frac {\Gamma \vdash \phi \land \psi} {\Gamma \vdash \phi} \text{(drop)} \]

Prove that this proof system is equivalent to the following proof system (which may be thought of as a fragment of IPL over \(\to\) and \(\land\)):

\[ \frac {} {\phi \vdash \phi} \text{(start)} \qquad \frac {\Gamma \vdash \phi} {\pi(\Gamma) \vdash \phi} \text{(exchg)} \qquad \frac { \Gamma \vdash \phi } { \Gamma, \psi \vdash \phi } \text{(weakn)} \qquad \frac {\Gamma, \phi, \phi \vdash \psi} {\Gamma, \phi \vdash \psi} \text{(contr)} \]

\begin{align*} \frac {\Gamma, \phi \vdash \psi} {\Gamma \vdash \phi \to \psi} \text{($\to$-intro)} \qquad \frac {\Gamma \vdash \phi \to \psi \qquad \Delta \vdash \phi} {\Gamma, \Delta \vdash \psi} \text{($\to$-elim)} \end{align*} \begin{align*} \frac {\Gamma \vdash \phi \qquad \Delta \vdash \psi} {\Gamma, \Delta \vdash \phi \land \psi} \text{($\land$-intro)} \qquad \frac { \Gamma \vdash \phi \land \psi \qquad \Delta, \phi, \psi \vdash \xi } { \Gamma, \Delta \vdash \xi } \text{($\land$-elim)} \end{align*}

This requires showing that the rules in one system are admissible in the other. This does not require structural induction. You should be able to build derivations which simulate the rules given certain assumptions (see the reading from this week for some examples of this). You may use without proof the following admissible rule in the second system:

\[ \frac {\Gamma \vdash \phi} {\Delta \vdash \phi} \text{(genContr)} \]

where \(\Delta\) is contained in \(\Gamma\).

4. Heap-Based Semantics

(Optional) Considing the following variant of a linear type system. It is essentially the system which Curry-Howard corresponds to the logic from the previous problem, but with an addition unit type so that we can write non-trivial programs. Note that the ⊤-elimination rule is trivial, but is required for the semantics so that we can model allocation/deallocation.

syntax:

<v>  ::= x | y | z | w | a | b | c | ...
<t>  ::=| <v> | λ <v> . <t> | <t> <t> | <t> , <t>
       | case <t> of <v> , <v> → <t>
       | case <t> of ● → <t>
       | clone(<t>) | drop(<t>)
<ty> ::=| <ty> ∧ <ty> | <ty> → <ty>

type system:

\[ \frac {} {x : A \vdash x : A} \text{(start)} \qquad \frac {\Gamma \vdash M : A} {\pi(\Gamma) \vdash M : A} \text{(exchg)} \]

\[ \frac {} {\vdash \bullet : \top} \text{($\top$-intro)} \qquad \frac {\Gamma \vdash M : \top \qquad \Delta \vdash N : A } {\Gamma, \Delta \vdash \texttt{case } M \texttt{ of } \bullet \to N : A} \text{($\top$-elim)} \]

\[ \frac {\Gamma, x : A \vdash M : B} {\Gamma \vdash \lambda x . M : A \to B} \text{($\to$-intro)} \qquad \frac { \Gamma \vdash M : A \to B \qquad \Delta \vdash N : A } { \Gamma, \Delta \vdash M N : B } \text{($\to$-elim)} \] \[ \hspace{-3mm} \frac { \Gamma \vdash M : A \qquad \Delta \vdash N : B } {\Gamma, \Delta \vdash M, N : A \land B} \text{($\land$-intro)} \quad \frac { \Gamma \vdash M: A \land B \qquad \Delta, x : A, y : B \vdash N : C } { \Gamma, \Delta \vdash \texttt{case } M \texttt{ of } x, y \to N : C } \text{($\land$-elim)} \] \[ \frac {\Gamma \vdash M : A} {\Gamma \vdash \texttt{clone}(M) : A \land A} \text{(clone)} \qquad \frac {\Gamma \vdash M : A \land B} {\Gamma \vdash \texttt{drop}(M): A} \text{(drop)} \]

Following this paper by Turner and Wadler, we can give a heap-based semantics to this system. The idea: we define a big-step relation \(\{ H \} M \Downarrow \{ H \} x\) where \(H\) is a unordered mapping from variables to values (i.e., a unit, function, or pair of values). This mapping represents the heap, and the right-hand side of the relation is always a variable, thought of as a pointer to a value on the heap.

I've taken some heavy liberties in defining this system, so we lose many of the guarantees that the original paper proves, but it is sufficient to model a simple version of clone and drop.

In the following rules, fresh means that there is no clash with any variables that appear in the given expression.

values:

<val> ::= λ<v> . <e> | <val> , <val> |

big-step semantics:

\[ \frac {} {\{H\} x \Downarrow \{ H \} x } \qquad \frac {\text{$y$ is fresh}} {\{H\} \lambda x . M \Downarrow \{ H, y \mapsto \lambda x . M \} y} \] \[ \frac {\text{$x$ is fresh}} {\{H\} \bullet \Downarrow \{ H, x \mapsto \bullet\}x} \qquad \frac { \{H\} M \Downarrow \{ H', x \mapsto \bullet\} x \qquad \{H'\} N \Downarrow \{ H'' \}y } { \{H\} \texttt{case } M \texttt{ of } \bullet \to N \Downarrow \{ H'' \}y } \qquad \frac {} {} \] \[ \frac { \{H\} M \Downarrow \{ H' \} x \qquad \{H'\} N \Downarrow \{ H'', x \mapsto \lambda y. M' \}z \qquad \{H''\} M'[z / y] \Downarrow \{ H'''\} w } { \{ H \} M N \Downarrow \{ H''' \} w } \] \[ \frac { \{ H \} M \Downarrow \{ H' \} x \qquad \{ H' \} N \Downarrow \{ H'', x \mapsto v_1, y \mapsto v_2 \} y } { \{ H \} (M, N) \Downarrow \{ H'', z \mapsto (v_1, v_2) \} z } \] \[ \hspace{-11mm} \frac { \{ H \} M \Downarrow \{ H', z \mapsto (v_1, v_2) \} z \qquad \text{$q$, $r$ are fresh} \qquad \{ H', q \mapsto v_1, r \mapsto v_2 \} N[q / x] [r / y] \Downarrow \{ H'' \} w } { \{ H \} \texttt{case } M \texttt{ of } x, y \to N \Downarrow \{ H'' \}w } \] \[ \frac { \{ H \} M \Downarrow \{ H', x \mapsto v \} x } { \{ H \} \texttt{clone}(M) \Downarrow \{ H', x \mapsto (v, v) \} x } \] \[ \frac { \{H\} M \Downarrow \{ H', x \mapsto (v_1, v_2) \} x } { \{ H \} \texttt{drop}(M) \Downarrow \{ H', x \mapsto v_1 \} z } \]

Give a derivation of the following judgment, also determining the heap \(H\).

\[ \{\texttt{x} \mapsto \bullet \} \texttt{case clone(x) of x, y → drop(x, y)} \Downarrow \{H\} \texttt{z} \]

Note that, since variables are chosen to be fresh in many rules above, it is not required that the derivation end in the variable z specifically, but it should be a variable which points to a value on the heap.